STRATEGI BERSAING DALAM MENINGKATKAN JUMLAH NASABAH PT. BANK SUMUT CABANG SYARIAH PADANGSIDIMPUAN - BUDI GAUTAMA SIREGAR (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2017)
The research problem is how the Bank  Sumut Cabang Syariah Padangsidimpuan create clean strategy in increasing the number of customers. while the goal is to figure out the strategy and the efforts made by the Bank Sumut Cabang Syariah Padangsidimpuan in increasing the number of customers. This study was descriptive qualitative research subjects is a common part of employees, bank customers Sharia Branch Padangsidimpuan North Sumatra. While data collection techniques are interviews, observation and documentation. The results of this study showed that the strategy of the Bank of North Sumatra Sharia Branch Padangsidimpuan in creating a competitive advantage in an effort to increase the number of customers is to adopt a strategy of focus, such as with the results of the financing which is cheaper than the banks of other Islamic or conventional banks, implementing network systems online so ease of service to customers and provide operational vehicles through mobile branch that services performed by meet the customers directly